Developing an integrated technology-environment-economics model to simulate food-energy-water systems in Corn Belt watersheds. (September 2021) - Li, Shaobin; Cai, Ximing; Emaminejad, Seyed Aryan; Juneja, Ankita; Niroula, Sundar; Oh, Seojeong; Wallington, Kevin; Cusick, Roland D.; Gramig, Benjamin M.; John, Stephen; McIsaac, Gregory F.; Singh, Vijay
Abstract: To facilitate understanding and decision making in the food-energy-water (FEW) nexus context, we develop an integrated technology-environment-economics model (ITEEM) at a watershed scale. ITEEM is built as an integration of various models, including models for grain processing, drinking water treatment, and wastewater treatment (technology); a watershed model for hydrology, water quality, crop production, and nutrient cycling (environment); an economics model assessing total benefit, including non-market valuation of environmental benefits. Different data techniques are applied to develop suitable surrogates for computer-based models, including a response matrix method, artificial neural networks, and lookup tables. Empirical equations are applied to develop models of economics and drinking water treatment. The input-output relationships between the models are formulated in a unified computational framework. ITEEM, a spatially semi-distributed dynamic simulation model, can be used to quantify the environmental and socioeconomic impacts of various management practices, technologies, and policy interventions on FEW systems in the Corn Belt. Highlights: Selected data techniques are applied to develop suitable surrogates for different process models. The integrated Technology-Environment-Economics model based on surrogates is computationally tractable. Insights on surrogate-based model coupling and tradeoffs of integration design choice are discussed. The integrated model is demonstrated for FEW systems in the Corn Belt. The sensitivity of 16 key parameters from component models on the integrated model is evaluated.